The Role of Molecular Analysis in the Diagnosis and Surveillance of Pancreatic Cystic Neoplasms - Winner, Megan; Sethi, Amrita; Poneros, John M; Stavropoulos, Stavros N; Francisco, Peter; Lightdale, Charles J; Allendorf, John D; Stevens, Peter D; Gonda, Tamas A (JOP. Journal of the Pancreas, 2015)
Context Molecular analysis of pancreatic cyst fluid obtained by EUS-FNA may increase diagnostic accuracy. We evaluated the utility of cyst-fluid molecular analysis, including mutational analysis of K-ras, loss of heterozygosity (LOH) at tumor suppressor loci, and DNA content in the diagnoses and surveillance of pancreatic cysts. Methods We retrospectively reviewed the Columbia University Pancreas Center database for all patients who underwent EUS/FNA for the evaluation of pancreatic cystic lesions followed by surgical resection or surveillance between 2006-2011. We compared accuracy of molecular analysis for mucinous etiology and malignant behavior to cyst-fluid CEA and cytology and surgical pathology in resected tumors. We recorded changes in molecular features over serial encounters in tumors under surveillance. Differences across groups were compared using Student’s t or the Mann-Whitney U test for continuous variables and the Fisher’s exact test for binary variables. Results Among 40 resected cysts with intermediate-risk features, molecular characteristics increased the diagnostic yield of EUS-FNA (n=11) but identified mucinous cysts less accurately than cyst fluid CEA (P=0.21 vs. 0.03). The combination of a K-ras mutation and ≥2 loss of heterozygosity was highly specific (96%) but insensitive for malignant behavior (50%). Initial data on surveillance (n=16) suggests that molecular changes occur frequently, and do not correlate with changes in cyst size, morphology, or CEA. Conclusions In intermediate-risk pancreatic cysts, the presence of a K-ras mutation or loss of heterozygosity suggests mucinous etiology. K-ras mutation plus ≥2 loss of heterozygosity is strongly associated with malignancy, but sensitivity is low; while the presence of these mutations may be helpful, negative findings are uninformative. Molecular changes are observed in the course of cyst surveillance, which may be significant in long-term follow-up. Image: Herbert Irving Comprehensive Cancer Center, Columbia University. New York, NY, USA.